PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT SATWA MAJU SEJAHTERA SEMPURNA BOGOR - Syaiful Anwar; Muchammad Hamdani; Muhlis Muhlis; Eka Sulistiawati (Economicus : Jurnal Ekonomi dan Manajemen, 2023)
The purpose of this research is (1) to determine the influence of the work environment on employee performance at PT Satwa Maju Sejahtera Sempurna (2) to determine the influence of work motivation on employee performance at PT Satwa Maju Sejahtera Sempurna (3) to determine the influence of the work environment and work motivation simultaneously on employee performance of PT Satwa Maju Sejahtera Sempurna (4) to find out the most dominant factors influencing the performance of employees of PT Satwa Maju Sejahtera Sempurna. The research results show that: (1) The coefficient of the work environment variable (X1) is 0.016, meaning that every time there is an increase in the variable X1 (Work Environment) by 1%, employee performance increases by 0.016 (1.6%) or vice versa every time there is a decrease in the variable X1 (Work Environment) of 1%, employee performance decreases by 0.016 (1.6%). (2) The coefficient of the work motivation variable (X2) is 0.386, meaning that every time there is an increase in the variable 1% then employee performance decreases by 0.386 (38.6%). (3) Simultaneous test results show that the Fcount value is 9.036 > Ftable 3.19 so that Ha is accepted and Ho is rejected, which means that the work environment variables and work motivation together have a significant effect on performance.